Latent Class Model on Socio-Religious Data - Bushra Shamshad; Junaid Saghir Siddiqi (Journal of Basic & Applied Sciences, 2018)
We believe that in last two decades perception regarding socio-religious values had been changed in our society. Survey has been carried out on “changes in social values and their acceptance” in year 2011. Respondents have asked 74 questions (marked on Likert-scale) regarding educational system, political and religious affiliations and their impact on social values. Among these we have selected only those questions related to socio-religious issues (based on of individual and collective perceptions about the prevailing standard of the society in comparison with Islamic standards). Similar surveys using the same questionnaire had had conducted in year 1994 and 2001. Respondents, at each time of survey, were young students (youth acquiring education) from different colleges (Karachi region) and Karachi University. Perception can be explained more appropriately through latent class model (LCM). Through LCM we can explore structures in the data in term of different opinion groups. The modeling is done on the selected set of similar questions from each year. Conditional probabilities for year 2011, 2001 and 1994 are then compared in search of presence of any difference of opinion between the respondents. It is observed that by the passage of time, due to the influence of the electronic media there is a change in the opinion about the values of the society among the youth. Although, there is a reduction in the proportion of “Dissatisfied group” within the society but negative perception is penetrating among our young generation specifically about Ulmah and Imam’s role and women’s due rights toward society.